Kepribadian Dalam Teori Sigmound Freud Dan Nafsiologi Dalam Islam - Hamali, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2018)
Personality possessed by a person shows the totality of the individual's human nature, both in physical and psychological form as a distinction between one person and another, personality is formed from the results of the interaction of individuals with the individual's living environment. While in nafsiologi personality describes the overall character possessed by individuals who are Muslim, both those displayed in the form of visible and invisible behavior. The personality displayed by all Muslims as a result of the influence of his religion. In other words, personality is a mechanism that works in an individual because of how to think, behave, react and behave inseparably from his beliefs or beliefs, due to the beliefs he adheres to, including the personality structure